Necropolítica, autoritaritarismo e a responsabilidade internacional do Estado brasileiro no caso Dom e Bruno. - Cardoso, Julie Sales (Brasil, 2024)
The object of this study is the State's responsibility for the murders of indigenist Bruno Pereira and British journalist Dom Phillips, that occurred in Vale do Javari, before the inter-American system of human rights protection, based on the concepts of necropolitics and authoritarianism. Jair Bolsonaro's government was marked by anti-indigenous policies and persecution of indigenous people and other activists who opposed his practices, therefore questions arose about the possible configuration of a necropolitics in this context, of which indigenous peoples would be victims, and so would be their allies, and which might have contributed to the murders of Dom and Bruno. Based on these issues, the research aims to highlight authoritarianism and necropolitics against indigenous people and indigenists in Brazil during Jair Bolsonaro's mandate, to then justify his responsibility for the aforementioned homicides, through a mainly comparative method of explanatory, quantitative and qualitative research, based on data, bibliographic and documentary sources. As for the result, there was the presence of authoritarianism and the attempt to erase indigenous peoples in the government of Jair Bolsonaro, which consisted of an extermination project. Specifically in relation to Vale do Javari, it was found that an exception zone was created through abandonment and intentional negligence, with the ignoring of reports about threats, resulting in the deaths of Dom and Bruno, for which there must be international accountability, given the several violations of the American Convention on Human Rights.